Flipped learning: A shift in graduate nursing education. Issue 1 (12th January 2022) - Murphy, Nancy; Strong, Caron; Jones, Gloria
ABSTRACT: The coronavirus (COVID-19) pandemic has caused a shift in education. Nursing education must respond to these changing times by redesigning classroom instruction. Flipped learning (FL) is a proposed method for teaching advanced practice nurses that is student-centered and engaging, both critical areas for contemporary learners. This qualitative study explored the perspectives and experiences of the family nurse practitioner faculty and the family nurse practitioner nursing students who participated in FL. The type and level of FL practices faculty can apply to support students coming to class prepared to engage in active learning activities was also investigated. The study used an insider action research design. There were two arms of the study, faculty and student. Ten faculty-led learning circles with four faculty and three family nurse practitioner student focus groups, each with six students, were held over the course of the study. Thematic findings were developed from both student and faculty data. The results revealed that family nurse practitioner students had a positive attitude toward FL. Many expressed FL provided perceptions of gained confidence, personalized learning, increased engagement, and preparedness for classroom instruction. Overall, faculty preferred FL over traditional teaching approaches. Several active learning activities were used by faculty with clinical case studies being the most preferred by student participants. This study confirms FL is a plausible and promising approach to traditional classroom instruction. However, more robust studies are needed to determine its benefits in advanced practice nursing education.